Ureaplasma and Mycoplasma in kidney allograft recipients—A case series and review of the literature. Issue 5 (15th June 2018) - Gerber, Lukas; Gaspert, Ariana; Braghetti, Antonio; Zwahlen, Hugo; Wüthrich, Rudolf; Zbinden, Reinhard; Mueller, Nicolas; Fehr, Thomas
Abstract: Ureaplasma urealyticum and Mycoplasma hominis are common inhabitants of the human genital tract. Increasingly, serious and sometimes fatal infections in immunocompromised hosts have been reported, highlighting their pathogenic potential. We reviewed the clinical impact of positive Ureaplasma spp. and Mycoplasma spp. urine cultures in 10 renal allograft recipients who presented with sterile leukocyturia. Five recipients remained asymptomatic. Five patients were symptomatic with dysuria or pain at the graft site. Three patients developed biopsy‐proven acute graft pyelonephritis with graft dysfunction. One of these patients additionally showed a renal abscess as demonstrated by magnetic resonance imaging (MRI). All were successfully treated. A literature search revealed a substantial number of case reports with severe and sometimes fatal Ureaplasma spp. or Mycoplasma spp. infections in immunocompromised patients. Colonization rate is high in renal transplant patients. A subset of patients is at risk for invasive disease.